Measurement of dielectric constant of silicon wafer using microwave non-destrictive testing and direct current technique: article / Nadia Md Kamal - Md Kamal, Nadia (2010)
This paper presents comparison between measurement of dielectric constant of silicon wafer by using MNDT which is at high frequency and by using HIOKJ 3532-50 LCR HiTESTER which at low frequency. Measurement of dielectric properties of silicon wafer at microwave frequencies is performed in free space using a pair of spot-focusing horn lens antennas, mode transitions, coaxial cable and vector network analyser (VNA). A contactless and non-destructive microwave method has been developed to characterize silicon semiconductor wafer from reflection and transmission measurement made in free space at normal incident. In this method, the free-space reflection and transmission coefficients, Sn and S2i are measured for silicon wafer sandwiched between two teflon plates which are quarter-wavelength at mid-band. The actual reflection and transmission coefficient, Sn and S2i of the silicon wafers are calculated from the measured Sn and S2i of the teflon plate-silicon wafer-teflon plate assembly in which the complex permittivity and thickness of the teflon plates are known. Result for p-type and n-type doped silicon wafer are reported in frequency range of 10GHz to 12GHz. As a comparison, a measurement at low frequency using DC method has been conducted. The frequency range is reported from 0.1 kHz to 50 kHz.